Household Income Diversification and Food Insecurity: A Case Study of Afghanistan - Rohullah Niazi; Aijun Liu; Jiqin Han; Sherouk Hassan; Hamidullah Elham; Maurice Osewe (Foods, 2025)
Strategies for income diversification are crucial in enhancing resilience to food insecurity, particularly in developing countries like Afghanistan, where resource scarcity and socio-political conflicts hinder economic stability. This study examines the relationship between income diversification and household food insecurity in Helmand, Afghanistan. Using cross-sectional survey data from 302 household heads, multivariate ordered logistic regression analysis was conducted to assess the association between income diversification and household food insecurity. Results indicate that households with lower income diversification are more likely to experience severe food insecurity. Additionally, factors such as illiteracy, lack of land ownership, unchanged income from the previous year, the absence of relatives in government jobs, poor financial situation, higher numbers of female household members, and greater distance from the district bazaar were associated with increased food insecurity. The findings suggest that while income diversification plays a vital role in mitigating food insecurity, it is insufficient alone for some households. The study concludes with recommendations to promote income diversification, improve education, facilitate land distribution, expand government employment programs, empower women, and improve market access and infrastructure in regions like Helmand to combat food insecurity.